Switching to Dolutegravir/lamivudine or Bictegravir/Emtricitabine/Tenofovir alafenamide. A comparative real-world study - Hernando Knobel; Esperanza Cañas-Ruano; Ana Guelar; Pablo Knobel; Judit Villar-García; Alicia González-Mena; Ceclia Canepa; Itziar Arrieta-Aldea; Augustin Marcos; Agustí Abalat-Torrres; Roberto Güerri-Fernández (HIV Research & Clinical Practice)
Background This real-world study compared the safety and effectiveness of Dolutegravir/lamivudine (D/L) and Bictegravir/Emtricitabine/Tenefovir alafenamide (B/F/T) switch therapy regimens for people living with HIV (PLWH) Methods The retrospective study conducted from April 2019 to November 2022, included PLWH with < 50 copies/mL of HIV-RNA prior to recruitment who initiated either D/L or B/F/T switching therapy. The primary objective was to evaluate treatment discontinuation rates; safety and virologic outcomes were also evaluated. Results 690 PLWH were included, 358 in the D/L and 332 in the B/F/T, and a median follow-up of 728 and 1013 days, respectively. The discontinuation proportions were 8.7% (31 participants, incidence rate of 4.44 per 100 PYFU in the D/L group and 15.3% (51 participants, incidence rate of 6.25 per 100 PYFU) in the B/F/T group. The adjusted hazard ratio for B/F/T discontinuation compared to D/L was 1.20 (95% CI: 0.71;2.0; p = 0.494). Virologic failure (VL > 200 copies/mL in two consecutive measurements) occurred in 1.1% and 0.9% of patients in the D/L and B/F/T groups, respectively. Notably, one patient in D/L group with severe non-adherence and virologic failure developed resistance mutations. Conclusions Switching to either B/T/F or D/L treatment for PLWH was effective and well tolerated in this real-world study. Treatment discontinuation rates did not significantly differ between the two regimens.